Electronic Coherence and Coherent Dephasing in the Optical Control of Electrons in Graphene - Heide, Christian; Eckstein, Timo; Boolakee, Tobias; Gerner, Constanze; Weber, Heiko B.; Franco, Ignacio; Hommelhoff, Peter (Nano Letters, 2021)
Electronic coherence is of utmost importance for the access and control of quantum-mechanical solid-state properties. Using a purely electronic observable, the photocurrent, we measure a lower bound of the electronic coherence time of 22 ± 4 fs in graphene. The photocurrent is ideally suited to measure electronic coherence, as it is a direct result of coherent quantum-path interference, controlled by the delay between two ultrashort two-color laser pulses. The maximum delay for which interference between the population amplitude injected by the first pulse interferes with that generated by the second pulse determines the electronic coherence time. In particular, numerical simulations reveal that the experimental data yields a lower bound on the electronic coherence time, masked by coherent dephasing due to the broadband absorption in graphene. We expect that our results will significantly advance the understanding of coherent quantum control in solid-state systems ranging from excitation with weak fields to strongly driven system
Keywords: graphene; quantum-path interference; electronic coherence time; quantum control